THE DUAL IMPACT OF OIL PRICE VOLATILITY ON IRAQ'S GROSS DOMESTIC PRODUCT: AN EMPIRICAL ANALYSIS FOR THE PERIOD 2010-2023 - Sabah Ahmed Asmaeel (Universitas Negeri Malang, 2026)
The Iraqi economy is heavily dependent on crude oil revenues, which constitute the primary source of funding for government expenditures and development projects. This study examines the impact of oil price fluctuations on Iraq's Gross Domestic Product (GDP), which serves as a key indicator of sustainable economic development. A quantitative research approach was employed using the Autoregressive Distributed Lag (ARDL) model to analyze the relationship between oil prices and GDP over the period 2010–2023. The empirical findings indicate that, in the short run, a one-unit increase in oil prices leads to an approximately ten-unit increase in GDP, demonstrating a significant positive relationship. However, the long-run analysis reveals an inverse relationship between oil prices and GDP, suggesting that excessive dependence on oil revenues may undermine long-term economic sustainability. The findings highlight the importance of utilizing oil revenues more efficiently by strengthening investment in productive sectors, improving governance, reducing the effects of corruption, and promoting economic diversification. Furthermore, infrastructure reconstruction and effective fiscal management are essential for transforming oil wealth into sustainable economic growth.